Relationship Between Spiritual Intelligence with Resilience in Teenagers Born in Poor Families - Chelsie Ireine Finka; Berta Esti Ari Prasetya (PSIKODIMENSIA, 2018)
This research is aimed at understanding relationship between spiritual intelligence and resilience of teenagers born in poor family in Jongin Village, Tolitoli Regency, Central Sulawesi. There are 39 participants in this research, and data collecting technique uses accidental sampling technique. Resilience variable is measured with resilience scale adapted from Resilience Quotation (RQ) and Spiritual Intelligence scale is measured with scale of Spiritual Intelligence Self-Report Inventory (SISRI-24). The data is analyzed with correlation technique of Product Moment Pearson. Correlation coefficient is r = 0.654 (p < 0,01), so it can be concluded that there is positive relationship and very significance between spiritual intelligence and resilience of teenagers born in poor family in Jongin Village, Tolitoli Regency, Central Sulawesi. The higher spiritual intelligence, the higher resilience will be; and the lower spiritual intelligence, the lower resilience will be